Can Higher Reserves Help Reduce Exchange Rate Volatility? - Nowak, M. (IMF Working Papers; Working Paper, 2004)
This paper studies the role of an increase in foreign exchange reserves in reducing currency volatility for emerging market countries. The study employs a panel of 28 countries over the period 1986-2002. Several control variables are introduced in the regressions to account for other factors affecting exchange rate volatility (monetary and external indicators as well as conventional macroeconomic fundamentals). The paper controls for the endogeneity induced by the role of the exchange rate regime, since the regime can affect both the level of reserves and exchange rate volatility. The results provide ample support for the proposition that holding adequate reserves reduces exchange rate volatility. The effect is strong and robust; moreover, it is nonlinear and appears to operate through a signaling effect.